The Effects of Family Issues and Supervisor Support on Work Satisfaction and Work Innovation: A Driver Intention to Remain? - Wulandari, Fitri (Universitas Muhammadiyah Yogyakarta, 2020)
The objective of this research to conduct an investigation of the impacts and relationships between family issues and supervisor support to develop work intention to remain within mediation variables are work satisfaction and work innovation. This research was used nonprobability sampling as a method, with 203 samples of employees on industrial manufacture company in Surakarta. Using Structural Equation Model (SEM) software application as a quantitative method to analyze the data. The result of this study indicates that there is a significant relationship between supervisor support to work satisfaction and work innovation, on the other hand, work satisfaction and work innovation significant relate into work intention to remain. Furthermore, this research also has resulted that work and family conflict does not significantly relate to work satisfaction, this result rejected the hypothesis. The conclusions for this study; First, consider the supervisor support importantly to develop and increase the level of work satisfaction and work intention to remain. Second, within work and family conflicts, the important variable that needs to be a concern was work conflict in case this indicates to decrease the level of work satisfaction. This result, indicate that compare with work innovation, the variable of work satisfaction was the most significant variable to impact the work intention to remain.